Increased Sucrose in the Hypocotyls of Radish Sprouts Contributes to Nitrogen Deficiency-Induced Anthocyanin Accumulation - Su, Nana; Wu, Qi; Cui, Jin (Frontiers in Plant Science, 2016)
Effects of nitrogen (N) deficiency and sucrose addition on regulation of anthocyanin biosynthesis and their relationship were investigated in this study. Radish sprouts subjected to N deficiency had 50% higher anthocyanin accumulation than when grown in Hoagland solution (a nutrient medium with all macronutrients). The contents of endogenous soluble sugars (sucrose, fructose and glucose) in the hypocotyls were also markedly increased by N limitation, with sucrose showing the highest increase. Inhibition of carbohydrate biosynthesis by addition of 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) also eliminated N deficiency-induced anthocyanin accumulation. The latter was further supported by the expression of anthocyanin biosynthesis related genes and decreased activities of nitrate reductase in the presence of sucrose. Together our results indicate that N deficiency-induced anthocyanin accumulation was, at least partly, dependent on the increase of the soluble sugar, especially Suc. This work is the first comprehensive study on relationship between N deficiency and sugar content on anthocyanin accumulation in the hypocotyls of radish sprouts.